2019
DOI: 10.1590/1980-5918.032.ao10
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain and risk factors during the third infancy

Abstract: Introduction: Low back pain is characterized as a pain in the area between the 12th rib and the low gluteal fold. This pain can affect different ages. During the growth peak, the postural control system is rearranged; therefore, the maintenance and fixation of these structures is crucial for the performance of daily activities. Thus, the prevalence of low back pain and their risk factors must be investigated, so that effective preventive measures against low back pain may be taken. Objective: To investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Another explanation could be that girls mature earlier than boys and that the hormonal changes that occur in the process alter their pain modulation and make them more susceptible to pain conditions [ 26 , 40 , 46 ]. In addition to these aspects, during pubertal development, children’s musculoskeletal structures are not mature enough to support the loads generated by growth, and this is also a critical period when most scoliosis or asymmetries of the body axis occur, which may contribute to the occurrence or increase in BP [ 18 , 46 ]. However, further research is needed to determine what circumstances during the onset of puberty may lead to an increase in reports of BP in girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation could be that girls mature earlier than boys and that the hormonal changes that occur in the process alter their pain modulation and make them more susceptible to pain conditions [ 26 , 40 , 46 ]. In addition to these aspects, during pubertal development, children’s musculoskeletal structures are not mature enough to support the loads generated by growth, and this is also a critical period when most scoliosis or asymmetries of the body axis occur, which may contribute to the occurrence or increase in BP [ 18 , 46 ]. However, further research is needed to determine what circumstances during the onset of puberty may lead to an increase in reports of BP in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the musculoskeletal structures of children at peak height velocity (PHV) are not mature enough to support the sudden mechanical load changes in the spine caused by the difference in growth rates between the legs and trunk, with the long bones of the legs experiencing a growth peak before the shorter bones of the trunk [ 18 , 19 ]. The development of muscles and the adaptation of ligaments and tendons to these new stresses also do not occur at the same rate.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review with participants aged between nine and sixteen showed a lifetime prevalence of 38.98% (11.60-85.56) [27]. Conversely, other studies have reported a 23% prevalence among children of the same age range (9.7 ± 2.3; n = 267) [28], 20% (n = 30) in a cohort of children between the ages of six and twelve [29], 5-7% in a younger cohort of boys and girls aged six to nine [30], and 9.01% (n = 36) in a cohort of students of 9.3 ± 1.87 (age interval 6-14 years) [31].…”
Section: Discussionmentioning
confidence: 94%
“…A systematic review with participants aged between nine and sixteen showed a lifetime prevalence of 38.98% (11.60–85.56) [ 27 ]. Conversely, other studies have reported a 23% prevalence among children of the same age range (9.7 ± 2.3; n = 267) [ 28 ], 20% ( n = 30) in a cohort of children between the ages of six and twelve [ 29 ], 5–7% in a younger cohort of boys and girls aged six to nine [ 30 ], and 9.01% ( n = 36) in a cohort of students of 9.3 ± 1.87 (age interval 6–14 years) [ 31 ].…”
Section: Discussionmentioning
confidence: 98%